Rickets with Dorfman-Chanarin syndrome - Taskin, Erdal; Akarsu, Saadet; Aygun, A. Denizmen; Ozlu, Ferda; Kilic, Mehmet (Karger, 2007)
Background: Dorfman-Chanarin syndrome is a rare, autosomal recessive, inherited, lipid storage disease. It is characterized by nonbullous congenital ichthyosiform erythroderma, leukocyte vacuoles and variable involvement of the liver, muscles and central nervous system, due to errors of triacylglycerol metabolism. To date only 32 cases of this syndrome have been described worldwide. Aims: To report the case of a boy with Dorfman-Chanarin syndrome with rickets. Case Report: A boy of Turkish origin was born of a nonconsanguineous marriage after an uncomplicated perinatal period. On examination the patient had failure to thrive, diffuse erythroderma and ichthyosis and clinical features suggesting rickets. A light-microscopic examination of peripheral smear revealed vacuolated leukocytes typical of Jordans' anomaly. Lipid analysis showed an increase in triacylglycerol and very low density lipoprotein. A radiographic study of the wrist revealed rickets. Conclusion: The clinical progression in these patients ranges from mild to fatal. We believe that patients with ichthyosis should be evaluated bearing in mind the possibility of Dorfman-Chanarin syndrome. This may increase the number of reported Dorfman-Chanarin syndrome cases, and the pathogenesis and progression of the disease will become clearer. Copyright (c) 2007 S. Karger AG, Basel.
Keywords: Dorfman-Chanarin syndrome; erythroderma, congenital ichthyosiform; leukocyte vacuoles; rickets